The Conceptualization of Mathematics in Sudoku Poetry by Puzi Hadi - Hashim, Noriani; Ain, Rosnidar (European Publisher, 2019)
This study is based on selected poems in Sudoku Puisi by Puzi Hadi. Sudoku poem is a kind of poem that has the characteristics of sudoku games by featuring mathematical concepts such as numbers and texts in poetry. Moreover, the audience is still less interested in and does not understand sudoku-type typography. Based on the researcher's observations, the typographical poems produced are quite complex including alphabets, characters, vocabulary, numbers, images and symbols that certainly have a somewhat critical meaning for the reader to understand. Selected poems are analyzed based on formalistic approach which focuses on form and content. All forms that are studied are based on sudoku games which involved problem solving by arranging numbers or alphabets on lines and rows in a poem. Next, based on the analysis, the researcher is able to explain the content of the poem which includes themes and questions. In addition, the researchers are able to interprete the meaning that the poet wishes to convey. This enables the authors’ thoughts to be brought forward in their attempts to present relevant ideologies and current issues. A combination of form and content found in literary work produce more interesting and meaningful poems for the readers. Sudoku type of poems stimulate logical thinking and expose new poets to creative and high-quality poems. Hence, through these poems, more readers who are not from the literature circle to appreciate the beauty of literature that is also meaningful. Lastly, the literary world will be buzzing with more readers from various backgrounds as they explore typography poems.